![\sqrt[8]{48^4}](https://tex.z-dn.net/?f=%20%5Csqrt%5B8%5D%7B48%5E4%7D%20)
can be rewritten as
![48^4](https://tex.z-dn.net/?f=%2048%5E4%20)
to the
![\frac{1}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B8%7D%20)
power:
![(48^4)^ \frac{1}{8}](https://tex.z-dn.net/?f=%2848%5E4%29%5E%20%5Cfrac%7B1%7D%7B8%7D%20)
Now, applying exponent rules (multiply exponent inside parentheses by the one outside parentheses), we get:
![(48^ \frac{1}{2})](https://tex.z-dn.net/?f=%2848%5E%20%5Cfrac%7B1%7D%7B2%7D%29%20)
This is equivalent to
![\sqrt{48}](https://tex.z-dn.net/?f=%20%5Csqrt%7B48%7D%20)
, so now, we just simplify:
![\sqrt{48}= \sqrt{16*3}= \sqrt{16}* \sqrt{3}=4 \sqrt{3}](https://tex.z-dn.net/?f=%20%5Csqrt%7B48%7D%3D%20%20%5Csqrt%7B16%2A3%7D%3D%20%5Csqrt%7B16%7D%2A%20%5Csqrt%7B3%7D%3D4%20%5Csqrt%7B3%7D)
So:
Answer:
![G(T(x)) = 27(x + 6.9)](https://tex.z-dn.net/?f=G%28T%28x%29%29%20%3D%2027%28x%20%2B%206.9%29)
Step-by-step explanation:
Given
![T(x) = 9(x + 6.9)](https://tex.z-dn.net/?f=T%28x%29%20%3D%209%28x%20%2B%206.9%29)
![G(x) = 3x](https://tex.z-dn.net/?f=G%28x%29%20%3D%203x)
Required [Missing from the question]
G(T(x))
We have:
![G(x) = 3x](https://tex.z-dn.net/?f=G%28x%29%20%3D%203x)
This implies that:
![G(T(x)) = 3(T(x))](https://tex.z-dn.net/?f=G%28T%28x%29%29%20%3D%203%28T%28x%29%29)
Substitute: ![T(x) = 9(x + 6.9)](https://tex.z-dn.net/?f=T%28x%29%20%3D%209%28x%20%2B%206.9%29)
![G(T(x)) = 3[9(x + 6.9)]](https://tex.z-dn.net/?f=G%28T%28x%29%29%20%3D%203%5B9%28x%20%2B%206.9%29%5D)
Open bracket
![G(T(x)) = 27(x + 6.9)](https://tex.z-dn.net/?f=G%28T%28x%29%29%20%3D%2027%28x%20%2B%206.9%29)
0.1 / 100 * 10 = 0.01 pounds
Answer:
(0, 4)
Step-by-step explanation:
To find the intersection of two lines, we want to find the value when they equal each other. To do this, we want to set the equations equal to each other.
First, let's simplify y = x + 4x + 4 by combining the x's.
y = 5x + 4
Now let's set the equations equal to each other. Since they both equal y, we can set the opposite sides equal to each other.
5x + 4 = 2x + 4
Now you want to combine the terms.
[subtract 4] 5x = 2x
[subtract 2x] 3x = 0
Now you want to isolate the x.
[divide by 3] x = 0
Now we want to find y by plugging x = 0 back into the equations.
y = 5(0) + 4
[multiply] y = 0 + 4
[add] y = 4
Check this with the other equation.
y = 2(0) + 4
[multiply] y = 0 + 4
[add] y = 4
Your answer is correct!
(0, 4)